Application of Ultra-Wideband Double Layer Printed Antenna for Partial Discharge Detection - Yuda Muhammad Hamdani; Umar Khayam (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Partial discharge (PD) is a local electrification phenomenon that partially connects insulation between the conductors and occurs either on the surface of the conductor or inside the insulation (void). During the PD there are several phenomena that accompany the occurrence of PD, such as impulse currents, heat radiation, electromagnetic waves, mechanical waves and chemical processes. This phenomenon is detected and measured to know the existence of PD. One of the PD measurements is ultra high frequency (UHF) method, by measuring the waves generated by PD using antenna. One of antenna having good characteristics is UWB double layer printed antenna. In this paper the application of ultra-wideband double layer printed antenna for partial discharge detection is reported. The application of antenna on PD measurement, shows that the antenna is able to detect PD. The characteristics of PD: PDIV, PDEV, PD waveform are measured using this antenna. Ultra-wideband (UWB) double layer printed antenna is an antenna developed from a square microstrip antenna with symmetrical T-shaped tethering. The proposed antenna is implemented on Epoxy FR-4 substrate with permittivity of 4.3, thickness of 1.6mm, and 72.8mm x 60.0mm in size. The VNA testing of the antenna shows that the antenna bandwidth is from 50MHz to 2.30GHz. The measured results of PD wave are PDIV, PD waveform and PDEV.